Acute cannabidiol treatment enhances social interaction in adult male mice - Livia F. Ferreira; Livia F. Ferreira; Nikhita Pathapati; Nikhita Pathapati; Stephen T. Schultz; Stephen T. Schultz; Mary C. Nunn; Mary C. Nunn; Bethany L. Pierce; Bethany L. Pierce; Yatzil R. Sanchez; Yatzil R. Sanchez; et al. (Frontiers Media S.A., 2023)
Cannabidiol (CBD) is a non-intoxicating phytochemical from Cannabis sativa that is increasingly used to manage pain. The potential for CBD to ameliorate dimensional behavior symptoms occurring in multiple psychiatric disorders was suggested, including social interaction impairments. To test this hypothesis, adult male BTBRT+Itpr3tf/J (BTBR) mice, a model of idiopathic autism exhibiting social preference deficits and restrictive repetitive behaviors, were acutely treated with vehicle or 0.1, 1, or 10 mg/kg CBD. Social interaction preference was assessed 50 min after treatment, followed by social novelty preference at 60 min, marble burying at 75 min and social dominance at 120 min. CBD (10 mg/kg) enhanced BTBR social interaction but not social novelty preference, marble burying or dominance, with serum levels = 29 ± 11 ng/mg at 3 h post-injection. Next, acute 10 mg/kg CBD was compared to vehicle treatment in male serotonin transporter (SERT) knock-out mice, since SERT deficiency is an autism risk factor, and in their wildtype background strain controls C57BL/6J mice. CBD treatment generally enhanced social interaction preference and attenuated social novelty preference, yet neither marble burying nor dominance was affected. These findings show acute treatment with as little as 10 mg/kg purified CBD can enhance social interaction preference in male mice that are otherwise socially deficient.